Trends in Steganography. - ZIELIŃSKA, ELŽBIETA; MAZURCZYK, WOJCIECH; SZCZYPI, KRZYSZTOF (Communications of the ACM, 2014)
The article discusses several trends in the field of steganography as of March 2014, focusing on data security breaches, computer hacking incidents, and efforts to develop methods for embedding secret data. According to the article, a large fraction of the security breaches in 2011 can be attributed to the Operation Shady RAT series of cyber attacks. Malware and the Stuxnet computer worm are mentioned. It states that steganography involves the presence of hidden messages in legitimate carriers such as JPEG files or HTML computer code.